An Investigation into a Link between Classroom Climate and Reading Achievement - RIA OKTAVIANI (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2018)
This research investigated a link between classroom climate and reading achievement, and discovered the influence of the classroom climate and reading achievement of the students at one junior high school in Palembang, South Sumatera, Indonesia. Fifty seven students participated in this study and were chosen by using convenience sampling method. In collecting the data, Constructivist Learning Environment Survey (CLES) and reading test were used. Descriptive statistics, Pearson Product Moment Correlation and regression analysis were employed to analyze the data. Based on the data analysis, it was found out that r (.175) <rtable (.260) was higher than 0.05. It designated that the classroom climate and students’ reading achievement were not significantly correlated. Since there was so significant link, it was not necessary to conduct further investigation, regression analysis, to check the influence of classroom climate and students’ reading achievement. It can be determined that classroom climate did not give substantial influence on students’ reading achievement.